František Hrubín's Lešanské jesličky in the light of text sources - Filipi, Michaela (Bohemica Olomucensia, 2013)
The paper deals with Hrubín's last poetry book Lešanské jesličky. Development of Hrubín's poetry culminates in this book - Hrubín's poetic principles are often being surpassed here and key themes are being completed. This is why Lešanské jesličky is so important work and why the author reconstructs the proces of writing and analyses text structure of the book.